The Influence of Formal and Informal Education in the Development of Islamic Psychology to Improve Community Welfare - Ashri Ramadhan; Tan, Ethan; Lima, Lucas (Darussalam: Journal of Psychology and Educational, 2024)
This study aims to analyze the influence of formal and informal education in the development of Islamic Psychology to improve community welfare, especially among Muslim communities in Yogyakarta City. Using a quantitative method with a survey approach, this study involved 300 respondents selected through a stratified random sampling method, including those who had experience in formal and informal faith-based education. Data was collected through a structured questionnaire that measured participants' perceptions of the impact of such education as well as their psychological well-being. The results of the analysis show that there is a significant positive relationship between formal and informal education in Islamic Psychology and psychological well-being. Formal education makes a strong contribution to the development of knowledge, while informal education, such as recitation and pesantren, plays a role in the formation of spiritual values that support individual well-being. The findings confirm the importance of integrating formal and informal education in the context of developing Islamic psychology to achieve better community well-being. This study also provides recommendations for educational institutions to further optimize the synergy between these two types of education.